Synthesis of ester prodrugs of 9-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]-2,6-diaminopurine (HPMPDAP) as anti-poxvirus agents - Krecmerová, Marcela; Holý, Antoín; Andrei, Graciela; Pomeisl, Karel; Tichý, Tomás; Brehová, Petra; Masojídková, Milena; Dracínský, Martin; Pohl, Radek; Laflamme, Genevieve; Naesens, Lieve; Hui, Hon; et al. (Journal of medicinal chemistry, 2010)
9-(S)-[3-Hydroxy-2-(phosphonomethoxy)propyl]-2,6-diaminopurine (HPMPDAP) and its cyclic form were selected for further evaluation as potential drug candidates against poxvirus infections. To increase bioavailability of these compounds, synthesis of their structurally diverse ester prodrugs was carried out: alkoxyalkyl (hexadecyloxypropyl, octadecyloxyethyl, hexadecyloxyethyl), pivaloyloxymethyl (POM), 2,2,2-trifluoroethyl, butylsalicylyl, and prodrugs based on peptidomimetics. Most HPMPDAP prodrugs were synthesized in the form of monoesters as well as the corresponding cyclic phosphonate esters. The activity was evaluated not only against vaccinia virus but also against different herpes viruses. The most potent and active prodrugs against vaccinia virus were the alkoxyalkyl ester derivatives of HPMPDAP, with 50% effective concentrations 400-600-fold lower than those of the parent compound. Prodrugs based on peptidomimetics, the 2,2,2-trifluoroethyl, the POM, and the butylsalicylyl derivatives, were able to inhibit vaccinia virus replication at 50% effective concentrations that were equivalent or ∼10-fold lower than those observed for the parent compounds.
Keywords: Antiviral Agents; proliferace buněk; Virology; Poxviridae; Adenine; Prodrugs; antivirové látky; Herpesviridae; Organophosphorus Compounds; Esters; Structure-Activity Relationship; lidé; Stereoisomerism; stereoizomerie; organofosforové sloučeniny; prekurzory léčiv; kultivované buňky; Cells, Cultured; virologie; adenin; RNA Viruses; Cell Proliferation; RNA-viry; vztahy mezi strukturou a aktivitou; estery; Humans